INVESTIGAÇÃO DA ATIVIDADE ANTI-INFLAMATÓRIA DA FRAÇÃO ACETATO DE ETILA E COMPOSTOS ISOLADOS DAS FOLHAS DA ESPÉCIE Punica granatum L. - PINHEIRO, Aruanã Joaquim Matheus Costa Rodrigues (2019)
The exacerbated adverse effects of anti-inflammatories justify the need to search for new drugs with these pharmacological actions. In this context, this work aims to evaluate the anti-inflammatory action of the ethyl acetate fraction and compounds isolated from leaves of the species Punica granatum L. For this, a hydroalcoholic extract was prepared from the leaves of the species with cold extraction and soon after it was fractionated using ethyl acetate as the solvent. Isolation of the compounds was performed by chromatographic methods and structural confirmation was given by mass spectrometry. Anti-inflammatory activity was performed in vivo using mice divided into groups; whether or not they were treated with the study drug and whether or not acute lung damage was induced by intratracheal instillation of lipopolysaccharide. The respiratory mechanics of the animals were evaluated by means of a mechanical respirator for small animals. In addition, bronchoalveolar lavage and lung lavage were collected for the analysis. The animals were weighed before and after the induction to evaluate the percentage of weight loss. The total leukocyte count was performed in the Neubauer chamber (blood and lavage); and differential blood smear and thick smear. The supernatant of the pulmonary macerate was used for IL-1b, IL-6, IL-8, IL-10 and TNF-α cytokine dosages by ELISA, gene expression of IL-1b, IL-6, IL-10 and TNF -α by qPCR in addition to total proteins by the Bradford method, and dosing of NF-kB and JNK signaling pathways by Western Blot. The histological analysis was by reading of blades stained in HE and Masson. The anti-inflammatory activity showed that the ethyl acetate fraction and the isolated compound reduced cell migration, mainly of neutrophils, to the lungs of the animals, besides improving pulmonary histology. The isolated compound also reduced weight loss in addition to the concentrations of total proteins, IL-1b, IL-6, IL-8 and TNF-α and reduced the expression of IL-1b, IL-6, and TNF-α. Finally, the isolated compound blocked the phosphorylation of the NF-kB and JNK signaling pathways, in addition to the respiratory mechanics of treated animals. In conclusion, the ethyl acetate fraction has been shown to be a potential anti-inflammatory agent, and the isolated compound should be further investigated for the formulation of a novel anti-inflammatory drug for the airways.